Underpotential Deposition From Fundamentals and Theory to Applications at the Nanoscale - Oviedo, Oscar Alejandro; Reinaudi, Luis; Garcia, Silvana; Leiva, Ezequiel Pedro Marcos (Monographs in Electrochemistry,, 2016)
With this volume, Ezequiel P. M. Leiva and co-authors fill a gap in the available literature, by providing a much-needed, comprehensive review of the relevant literature for electrochemists, materials scientists and energy researchers. For the first time, they present applications of underpotential deposition (UPD) on the nanoscale, such as nanoparticles and nanocavities, as well as for electrocatalysis. They also discuss real surface determinations and layer-by-layer growth of ultrathin films, as well as the very latest modeling approaches to UPD based on nanothermodynamics, statistical mechanics, molecular dynamics and Monte-Carlo simulations.